The Role of Sigma-1 Receptor in Modulating Endoplasmic Reticulum Stress: Putative Relevance to Alzheimer Disease - Tassé, Louis-Alexandre (Université d'Ottawa / University of Ottawa, 2018)
Alzheimer’s Disease and other neurodegenerative diseases have been linked to dysfunction in proteostasis in the endoplasmic reticulum (ER). The ER provides an exclusive environment for protein synthesis and folding, which is vital to the cellular function. Under normal conditions, the synthesis and degradation of proteins remain in balance. During aging or during pathological states, disturbances of ER occur and consequently the failure of protein homeostasis. The cells rely on a system, the unfolded protein response (UPR), which regulates the homeostasis by three ER sensors: PERK, ATF6, and IRE-1. Perturbations of ER function result in UPR. In physiological condition, the cell may overcome the insult and regain homeostasis. However, prolonged or chronic UPR activates apoptotic pathways and may cause cell death. The sigma-1 receptor (Sig-1R) is a 25 kD polypeptide and a chaperone protein concentrated at the mitochondria-associated ER membrane domain (MAM). The Sig-1R plays significant roles governing calcium signalling, mitochondrial function, oxidative stress, protein chaperoning and ER stress. Results of this investigation demonstrate that immortalized mouse embryonic fibroblasts (MEFs) derived from Sig-1R-/—(KO) mice have higher baseline activation in all three branches of the UPR in the absence of ER stress compared to MEFs derived from Wild-type mice. Despite this increase in baseline activation, the PERK and ATF6 pathways have a significantly blunted response to acute stress. Rescue experiments by expressing the Sig-1R in KO MEFs did not recover the WT MEFs phenotype. Primary Sig-1R KO MEFs did not show baseline ER stress, but did show inhibited recovery following treatment with the acute ER stressor DTT. Overall, our data suggests that Sig-1R is important for the reestablishment of proteostasis following acute stress.
Keywords: ER stress; Sigma1-R